2018
DOI: 10.1016/j.bpj.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Structure and Composition Control Consequences of Interleaflet Coupling in Asymmetric Vesicles

Abstract: Using Förster resonance energy transfer, raft/liquid-ordered-domain formation was assessed in asymmetric vesicles containing outer leaflets composed of high-Tm (melting temperature) saturated phosphatidylcholines (diCPC, diCPC, diCPC, or diCPC), low-Tm unsaturated dioleoylphosphatidylcholine (DOPC) and cholesterol, and inner leaflets composed of lipids that by themselves would not form ordered domains (DOPC and cholesterol). Ordered-domain formation in the outer leaflet was compared to that in symmetric vesicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(83 citation statements)
references
References 52 publications
5
78
0
Order By: Relevance
“…In a sense, different researchers describe leaflet coupling for a particular system without an agreed definition of what ''coupling'' means. Beyond phase-separated domains in the two leaflets being in register, coupling can mean that one phase influences the melting temperature (4,41) or the diffusion coefficient of the apposed leaflet (42), the order parameter in the apposed leaflet is changed (41,42), or that the extent of interdigitation has changed (42). Nonetheless, theoretical/phenomenological models have been proposed to estimate coupling strengths (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…In a sense, different researchers describe leaflet coupling for a particular system without an agreed definition of what ''coupling'' means. Beyond phase-separated domains in the two leaflets being in register, coupling can mean that one phase influences the melting temperature (4,41) or the diffusion coefficient of the apposed leaflet (42), the order parameter in the apposed leaflet is changed (41,42), or that the extent of interdigitation has changed (42). Nonetheless, theoretical/phenomenological models have been proposed to estimate coupling strengths (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…WANG et al observed in asymmetric vesicles that the inhibition of outer-leaflet ordered-domain formation by inner-leaflet lipids decreased. He explains this by an increased ability of outer-leaflet lipids to form an ordered state by themselves (Wang and London, 2018). From coarse-grained molecular dynamics simulations Fowler et al (2016) proposed a two-step model in which membranes undergo a shift from an anti-registered phase to registered symmetric phase after bilayer equilibration.…”
Section: Discussionmentioning
confidence: 99%
“…If there are no domains, one would predict they should have had similar levels of activation. Second, studies in plasma membrane vesicles formed after lipid exchange and in artificial asymmetric lipid vesicles show that lipid compositions increasing the propensity to form Lo domains do result in increased formation of ordered lipid domains under physiologic or near physiologic conditions [42], [48]. Third, the domain model is favored by the close relationship between decreased sensitivity of IR activity to phosphatases in lipid substitutions that favor Lo domain formation.…”
Section: Discussionmentioning
confidence: 99%
“…This correlation can be seen clearly in Figure 4 in which IR autophosphorylation activity is graphed against the gel-to-Ld phase transition temperatures (Tm) [Supplementary table 2] of the lipids in vesicles containing a single lipid species. The gel state is highly ordered, and in artifical asymmetric membranes high Tm is associated with a greater tendency to form Lo domains when cholesterol is present [42].…”
Section: Strong Correlation Between Propensity To Form Ordered State Bilayers and Increased Ir Activitymentioning
confidence: 99%